Transmission channels of business cycles synchronization in an enlarged EMU - Iulia Traistaru (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
The accession of Central European countries to the European Union implies the possibility of euro area membership once the Maastricht nominal convergence criteria will be met. This raises the question about costs and benefits of an enlarged euro area. In particular, the prospects for structural and cyclical convergence in an enlarged euro area have been little investigated so far. How synchronized are business cycles between the Central European new EU countries (CE-EU- 8) and current euro area members? How is business cycles synchronization transmitted across these countries? This paper investigates the degree of business cycles synchronization between the current and future euro area member states over the period 1990-2003 and analyses the similarity of economic structures and bilateral trade intensity as main transmission channels. Using band-pass filtered GDP data, I find that business cycles between the CE-EU-8 countries and euro area members are less correlated in comparison to the current euro area members. In the group of the CE-EU-8 countries, over the analyzed period, business cycles in Hungary, Poland and Slovenia were closer correlated with the economic activity fluctuations in the current euro area members. The econometric analysis indicates that similarity of economic structures and bilateral trade intensity were positively and significantly associated with business cycles correlations. This result is robust to different groups of country pairs and estimation techniques. These empirical findings suggest that, to the extent shocks are country – specific, a common monetary policy might have asymmetric effects in an euro area extended early to the new EU members. This policy implication needs however two qualifications: the cost of adopting a common monetary policy depends first, on the extent to which the exchange rate can be used as an efficient shock absorber and second, on the extent to which monetary policy can be used effectively to stabilizing economic activity. Furthermore, the relationship between similarity of economic structures, bilateral trade intensity, on the one hand, and, business cycles synchronization, on the other hand, is found endogenous suggesting that, in the long term, convergence of economic structures and trade growth are expected. If the adoption of the euro will be well prepared it will bring significant benefits to the new EU countries.
Keywords: E32; F15; F33; F41; 330; Economic and Monetary Integration; Optimum Currency Area; Business Cycles; Sectoral Specialization